2016
DOI: 10.1007/8904_2016_572
|View full text |Cite
|
Sign up to set email alerts
|

Four Years of Diagnostic Challenges with Tetrahydrobiopterin Deficiencies in Iranian Patients

Abstract: Hyperphenylalaninemia (HPA) is a condition caused by tetrahydrobiopterin (BH 4 ) and phenylalanine hydroxylase (PAH) deficiencies. It is essential that differential diagnosis be conducted to distinguish these two causes of HPA, because BH 4 deficiency is a more severe disease involving progressive neurologic deterioration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…However, this patient had a low biopterin and neopterin levels in both plasma and CSF known as typical pattern. The homozygous mutations c.200C > T (p.Thr67Met) and c.84‐3C > G previously reported as severe form mutations from Albania, Italy, and Iran were detected in our PTPS deficiency patients who had normal neopterin and low biopterin levels in plasma 21,22,23,24 …”
Section: Discussionmentioning
confidence: 48%
“…However, this patient had a low biopterin and neopterin levels in both plasma and CSF known as typical pattern. The homozygous mutations c.200C > T (p.Thr67Met) and c.84‐3C > G previously reported as severe form mutations from Albania, Italy, and Iran were detected in our PTPS deficiency patients who had normal neopterin and low biopterin levels in plasma 21,22,23,24 …”
Section: Discussionmentioning
confidence: 48%
“…These findings align with previous reports from other countries in the region. A high incidence of BH 4 deficiency (~12%) was reported for the Kingdom of Saudi Arabia 22 and Iran 23 …”
Section: Discussionmentioning
confidence: 99%
“…In spite of the treatment, the blood l ‐Phe levels remained persistently increased and the patient continued to suffer seizures and neurodevelopmental delay. In fact, it has been reported that patients with DHPR may develop neurological symptoms even with blood l ‐Phe levels within the normal range 6 …”
Section: Discussionmentioning
confidence: 99%
“…Patients with DHPRD commonly have an early symptoms onset. The symptoms include hypotonia or trunk hypotonia, movement disorders (mainly dystonia) with distal hypertonia, parkinsonism/hypokinetic rigid syndrome (consisting of bradykinesia or hypokinesia), extrapyramidal rigidity (“cogwheel rigidity”), rest tremor, impaired motor development and cognitive impairment, irritability and mood swings, neonatal dysphagia, lethargy, delayed language acquisition, temperature‐control disorders, and myoclonic seizures 1,5,6 …”
Section: Introductionmentioning
confidence: 99%